SISTEMA FINANCEIRO: ABUSO DE PODER ECONÔMICO E IMPUNIDADE INSTITUCIONALIZADA - Aparecido de Oliveira Pereira; Shirley Oliveira Lima Nomura (Universidade do Oeste Paulista, 2012)
This study aims at identifying abusive practices performed by the Financial System. Destitute of basic ethics principles, the behavior breaks constitutional principles, especially articles 1, 3 and 170 of the Brazilian Federal Constitution. Supported by the lack of regulation on the system and by creation of laws that assist them injuring society, they disregard the ones in the lower classes on the social pyramid and try, in their business, to obtain illegal gains affecting the nation, through speculation or fraudulent processes. The National Monetary Council, whose social representation does not answer to law principles nor the wishes of society, can overwhelm the powers fixed by the constitution, notedly Judiciary and Legislative, putting the whole society on its knees during hard economic times.